2019
DOI: 10.1016/s1470-2045(18)30750-2
|View full text |Cite|
|
Sign up to set email alerts
|

Disease-free survival as a surrogate for overall survival in patients with HER2-positive, early breast cancer in trials of adjuvant trastuzumab for up to 1 year: a systematic review and meta-analysis

Abstract: International Drug Development Institute (their employer) during the conduct of the study. SD reports grants, personal fees, and non-financial support from Roche-Genentech, and grants and personal fees from Puma, outside of the submitted work. MP-G reports personal fees from Roche-Genentech, outside of the submitted work. DS reports consultancy for Novartis, Eli Lilly, and Seattle Genetics, and is a board member at BioMarin. NW reports grants from the National Cancer Institute, during the conduct of the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 27 publications
2
52
0
Order By: Relevance
“…At least four large, randomized, controlled clinical trials have demonstrated that women with early human epidermal growth factor receptor 2 (HER2)-positive breast cancer receiving 12-month adjuvant trastuzumab show improved disease-free survival (DFS) compared with those who did not receive this treatment 1 . Overall survival (OS) improved in agreement with DFS 2 . Although a longer duration of trastuzumab treatment of 24 months seems to add toxicity without additional survival benefit 3 , the shorter duration of a 9-week trastuzumab regimen only exhibited a borderline significant improvement in DFS 4 .…”
Section: Introductionmentioning
confidence: 62%
“…At least four large, randomized, controlled clinical trials have demonstrated that women with early human epidermal growth factor receptor 2 (HER2)-positive breast cancer receiving 12-month adjuvant trastuzumab show improved disease-free survival (DFS) compared with those who did not receive this treatment 1 . Overall survival (OS) improved in agreement with DFS 2 . Although a longer duration of trastuzumab treatment of 24 months seems to add toxicity without additional survival benefit 3 , the shorter duration of a 9-week trastuzumab regimen only exhibited a borderline significant improvement in DFS 4 .…”
Section: Introductionmentioning
confidence: 62%
“…However, this approach has been commonly used for surrogate validation, especially when the number of included trials was limited. 13,17,37 Furthermore, although our study focused on the trial-level association, the validity of a surrogate endpoint should be supported by both trial-level and individual-level associations. Additional analyses are warranted to reassess the individuallevel association between pCR and long-term outcomes in TNBC using updated data.…”
Section: Discussionmentioning
confidence: 98%
“…No included trial had separate non-inferiority margin for OS and in applying our same predefined DFS non-inferiority margin to OS results we are assuming we accept the same difference, which is debatable. While OS in our analysis did not meet our calculated non-inferiority threshold, DFS has been shown to be a good surrogate for OS in adjuvant HER2 positive breast cancer and longer follow up is needed to confirm [ 30 ]. GRADE recommendation for OS results is moderate due to serious imprecision of these results evidenced by wide 95%CI margins in the included trials.…”
Section: Discussionmentioning
confidence: 99%